Implications and Challenges of the Development of Mussel Farming (Mytella guyanensis: Mytilidae) in the Community of Isla Venado, Gulf of Nicoya (Biocenosis, 2022)
The Gulf of Nicoya is one of the richest marine sectors in the country. Large quantities of marine products have been extracted from its environment, contributing to food and the national economy. For many years there has been an alarming decrease in marine species which is an unsustainable. Therefore, the objective of the project is to seek the contribution in the community of Isla Venado, Gulf of Nicoya, using tools from aquaculture practices that are friendly to the environment through a cultivation system of the species Mytella guyanensis: Mytilidae in order to improve the economy and take care of the environment, generating at the same time inputs for future projects of conservation of natural resources in the community.
Keywords: community participation; natural resources; farming system; productivity; indiscriminate fishing